The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0093811
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis May Result in Selection Favouring the Products of Long-Distance Pollen Dispersal in Eucalyptus

Abstract: Using native trees from near the northern and southern extremities of the relatively continuous eastern distribution of Eucalyptus globulus in Tasmania, we compared the progenies derived from natural open-pollination (OP) with those generated from within-region and long-distance outcrossing. Controlled outcrossing amongst eight parents - with four parents from each of the northern and southern regions - was undertaken using a diallel mating scheme. The progeny were planted in two field trials located within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 114 publications
0
7
1
Order By: Relevance
“…This pattern observed for interspecific hybridisation contrasts with the positive heterosis observed for inter-provenance crosses within E. globulus (Volker et al 2008; Costa e Silva et al 2014).…”
contrasting
confidence: 78%
See 1 more Smart Citation
“…This pattern observed for interspecific hybridisation contrasts with the positive heterosis observed for inter-provenance crosses within E. globulus (Volker et al 2008; Costa e Silva et al 2014).…”
contrasting
confidence: 78%
“…Assisted migration involves moving species beyond their current range, or moving populations within a species range (sometimes referred to as 'assisted gene flow ' -Aitken & Bemmels 2016). Debate about the need for assisted migration and assisted gene flow in forest trees is ongoing, because it is possible that naturally occurring long-distance gene flow may be enough to facilitate rapid natural adaptation to climate change (Kremer et al 2012; Costa e Silva et al 2014). Certainly high levels of such gene flow have been noted among remnant eucalypt populations in highly fragmented landscapes in Western Australia (Sampson & Byrne 2008;Byrne et al 2008).…”
Section: Future Issuesmentioning
confidence: 99%
“…F < 0) often observed in wild eucalypt populations despite the excess of homozygosity in OP seed (see Potts and Wiltshire 1997). However, in the case of E. globulus, there is evidence of heterosis in inter-population crosses (Volker et al 2008;Costa e Silva et al 2014), suggesting that some mild build-up of ID within wild populations are likely due to bi-parental inbreeding (Hardner and Potts 1997;Mimura et al 2009), although the rare survival of selfs cannot be dismissed. The long-term monitoring of the field trial revealed a dynamic interplay between ID for survival (ID surv ) and ID for growth (height and DBH) of survivors (ID growth ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the changes caused by migration were found to be slow and to increase over time, and tended to be reduced with increased correlational selection and/or mutation correlation [30]. In the present case, the contribution of gene flow cannot be completely dismissed, considering: (i) E. globulus to be pollinated by animals, including a key bird pollinator which annually migrates between the Mainland and Island populations [67,99]; and (ii) the demonstrated potential for post-dispersal selection favoring the products of long-distance dispersal due to a release from inbreeding depression [100]. While the effective pollen dispersal curve has been shown to be fat-tailed, the average dispersal distance has been estimated as only between 69 m and 833 m, depending on the studied population [74].…”
Section: Discussionmentioning
confidence: 73%